Discovery of potential biomarkers for osteoporosis using LC/GC−MS metabolomic methods - Wu, Yahui; Yuan, Chunhua; Han, Peipei; Guo, Jiangling; Wang, Yue; Chen, Cheng; Huang, Chuanjun; Zheng, Kai; Qi, Yiqiong; Li, Jiajin; Xue, Zhengjie; Lu, Fanchen; et al. (Frontiers in Endocrinology, 2024)
Purpose: For early diagnosis of osteoporosis (OP), plasma metabolomics of OP was studied by untargeted LC/GC-MS in a Chinese elderly population to find possible diagnostic biomarkers.Methods: A total of 379 Chinese community-dwelling older adults aged ≥65 years were recruited for this study. The BMD of the calcaneus was measured using quantitative ultrasound (QUS), and a T value ≤-2.5 was defined as OP. Twenty-nine men and 47 women with OP were screened, and 29 men and 36 women were matched according to age and BMI as normal controls using propensity matching. Plasma from these participants was first analysed by untargeted LC/GC-MS, followed by FC and P values to screen for differential metabolites and heatmaps and box plots to differentiate metabolites between groups. Finally, metabolic pathway enrichment analysis of differential metabolites was performed based on KEGG, and pathways with P≤0.05 were selected as enrichment pathways.We screened metabolites with FC>1.2 or FC<1/1.2 and P<0.05 and found 33 differential metabolites in elderly men and 30 differential metabolites in elderly women that could be potential biomarkers for OP. 2-Aminomuconic acid semialdehyde (AUC=0.72, 95% CI 0.582-0.857, P=0.004) is highly likely to be a biomarker for screening OP in older men.Tetradecanedioic acid (AUC=0.70, 95% CI 0.575-0.818, P=0.004) is highly likely to be a biomarker for screening OP in older women.These findings can be applied to clinical work through further validation studies.This study also shows that metabolomic analysis has great potential for application in the early 4 diagnosis and recurrence monitoring of OP in elderly individuals.